Inter actor relations in the veneration of Chinese Sea Goddess Mazu (媽祖, Māzǔ), at Tjoe Tik Kiong (慈德宮, Cí dé gōng) Temple, Pasuruan - Olivia; Oetomo, Dede; Koesbardiati, Toetik (Masyarakat, Kebudayaan dan Politik, 2025)
The Tjoe Tik Kiong Temple (慈德宮, Cídé Gōng) in Pasuruan City hosts veneration ritual activity for the Chinese Sea Goddess, Mazu (媽祖, Māzǔ). This study aims to examine the relationship between the actors behind the performance of the Mazu ritual shapes the dynamics of the change process over time. The paper explores how the actors revitalize each other and re-express their Chinese Indonesian identity in the worship of Mazu. Conducted between September 2022 and December 2024, this ethnographic study focuses on the key participants temple caretakers, local Chinese Indonesian devotees, cultural intermediaries, and younger generations who each play distinct roles in the ritual process. The data collection involved direct observation, interviews, and visual documentation during the fieldwork. The results show that the participants’ roles and relationships in the worship activities greatly influence changes and adaptations in the worship of Mazu. The Chinese Indonesian community’s expression of its identity, as articulated through its veneration of Mazu, serves as a testament to its ability to adapt to the contemporary demands of the present. This phenomenon ultimately contributes to the distinctive characteristics of Chinese communities in Indonesia, which differ from those found in other countries.